Cut-edge mucoperiosteal flap for anterior fixation of palatal flap in palatoplasty. Issue 3 (July 2018) - Elsherbiny, Mohamed; Saed, Basem; Sheir, Hesham; Elzohiri, Mohamed; El-Ghazaly, Mohamed
Abstract : Introduction: This study was done at Mansoura University Children Hospital, Egypt from the period of June 2013 to June 2015 on 80 patients with incomplete intramaxillary cleft palate. Patients and methods: After oral layer closure of the cleft palate, anterior fixation of the flap is obtained by raising the anterior cut-edge of mucoperiosteal flap for about 0.5 cm then suturing the flap to the elevated cut-edge with two stitches. We divided the patients into two groups and evaluated the time needed for fixation the palatal flap and difficulty of fixation and evaluated the incidence of anterior palatal fistula between the two groups. Results: The time used for elevation of the flap and taking the two stitches in group A ranged from 2.5 to 6 min. However, the time used for taking the two stitches without elevation of the flap in group B ranged from 2.8 to 9 min. Conclusion: We found that cut-edge mucoperiosteal flap for anterior fixation of two-flap palatoplasty is a simple step at the end of cleft palate repair procedure which allows easy fixation of the palatal flap with short time and good opposition of the tissue edges, allowing better healing.